2014
DOI: 10.2147/copd.s60182
|View full text |Cite
|
Sign up to set email alerts
|

Living in negotiation: patients’experiences of being in the diagnostic process of COPD

Abstract: PurposeTo illuminate patients’ lived experiences of going through the process of being diagnosed with chronic obstructive pulmonary disease (COPD).Patients and methodsA phenomenological-hermeneutic analysis was applied in the interpretation of interviews with eight persons diagnosed with mild or moderate COPD.ResultsOne main theme ‘living in negotiation’, and three themes ‘living with a body out of step with the diagnosis’, ‘dealing with the past’, and ‘being challenged by the future’ reflected the process par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(80 citation statements)
references
References 45 publications
1
74
0
5
Order By: Relevance
“…The number of studies of the experience of COPD in its initial stages is growing (Ansari et al., ; Arne et al., ; Berger et al., ; Lindgren, Storli, & Wiklund‐Gustin, ; Lindqvist & Hallberg, ). Although patients in this study were younger than participants in most of the earlier studies, the findings are in harmony with what has previously been revealed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of studies of the experience of COPD in its initial stages is growing (Ansari et al., ; Arne et al., ; Berger et al., ; Lindgren, Storli, & Wiklund‐Gustin, ; Lindqvist & Hallberg, ). Although patients in this study were younger than participants in most of the earlier studies, the findings are in harmony with what has previously been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Health professionals tend to misinterpret patients’ shame and failure to quit smoking as a lack of motivation to change (Halding et al., ). However, to respect people's own personal stories (Bailey et al., ) and be sensitive to addressing smoking cessation in a helpful, nonjudgemental way is of major importance (Gullick & Stainton, ; Jonsdottir et al., ; Lindgren et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10] People with COPD generally experience the diagnostic process as prolonged, and the diagnosis often creates uncertainty of what may happen in the future. [11] Some days are described to be "good", while other days can be "bad"; therefore, COPD is described as an uncontrolled disease. [12] As COPD progresses, there is often a strong fear of suffocation and death, and the patients feel that death is constantly "on their heels".…”
Section: Introductionmentioning
confidence: 99%